Preclinical pharmacokinetic evaluation to facilitate repurposing of tyrosine kinase inhibitors nilotinib and imatinib as antiviral agents - Hari Krishna Ananthula; Scott Parker; Erin Touchette; R. Mark Buller; Gopi Patel; Daniel Kalman; Johanna S. Salzer; Nadia Gallardo-Romero; Victoria Olson; Inger K. Damon; Tessa Moir-Savitz; Larry Sallans; et al. (BMC, 2018)
Abstract Background Several tyrosine kinase inhibitors (TKIs) developed as anti-cancer drugs, also have anti-viral activity due to their ability to disrupt productive replication and dissemination in infected cells. Consequently, such drugs are attractive candidates for "repurposing" as anti-viral agents. However, clinical evaluation of therapeutics against infectious agents associated with high mortality, but low or infrequent incidence, is often unfeasible. The United States Food and Drug Administration formulated the "Animal Rule" to facilitate use of validated animal models for conducting anti-viral efficacy studies. Methods To enable such efficacy studies of two clinically approved TKIs, nilotinib, and imatinib, we first conducted comprehensive pharmacokinetic (PK) studies in relevant rodent and non-rodent animal models. PK of these agents following intravenous and oral dosing were evaluated in C57BL/6 mice, prairie dogs, guinea pigs and Cynomolgus monkeys. Plasma samples were analyzed using an LC-MS/MS method. Secondarily, we evaluated the utility of allometry-based inter-species scaling derived from previously published data to predict the PK parameters, systemic clearance (CL) and the steady state volume of distribution (Vss) of these two drugs in prairie dogs, an animal model not tested thus far. Results Marked inter-species variability in PK parameters and resulting oral bioavailability was observed. In general, elimination half-lives of these agents in mice and guinea pigs were much shorter (1-3 h) relative to those in larger species such as prairie dogs and monkeys. The longer nilotinib elimination half-life in prairie dogs (i.v., 6.5 h and oral, 7.5 h), facilitated multiple dosing PK and safety assessment. The allometry-based predicted values of the Vss and CL were within 2.0 and 2.5-fold, respectively, of the observed values. Conclusions Our results suggest that prairie dogs and monkeys may be suitable rodent and non-rodent species to perform further efficacy testing of these TKIs against orthopoxvirus infections. The use of rodent models such as C57BL/6 mice and guinea pigs for assessing pre-clinical anti-viral efficacy of these two TKIs may be limited due to short elimination and/or low oral bioavailability. Allometry-based correlations, derived from existing literature data, may provide initial estimates, which may serve as a useful guide for pre-clinical PK studies in untested animal models.